PELATIHAN IMPLEMENTASI PESANTREN BERBASIS RISET PADA YAYASAN ZAINUL HASAN GENGGONG PROBOLINGGO - Sobri, Ahmad Yusuf; Taufiq, Ahmad; Sopingi, Sopingi; Saputra, Nur Mega Aris; 'Ilmi, Achmad Miftachul; Muslihati, Muslihati (Universitas Negeri Surabaya, 2024)
This community service activity aims to implement a research-based Islamic boarding school model at the Zainul Hasan Genggong Education Foundation. The focus of this activity is based on the results of the condition analysis shown by the Zainul Hasan Education Foundation which is working to develop a research-oriented madrasa system in every learning implementation. The Madrasah Research Program is one of the flagship programs of the Ministry of Religion of the Republic of Indonesia. The specialty of this research-based Islamic boarding school is the integration of research projects in learning which aims to train students to be able to write scientific papers and research studies. The program is intended to provide a learning environment that is able to boost students' 21st century skills, namely the ability to think critically, creatively, collaboratively, communicate well, be culturally intelligent and be technologically skilled. Therefore, it is necessary to conduct research-based Islamic boarding school implementation training at the Zainul Hasan Foundation. The training implementation method consists of stages (a) training preparation; (b) socialization; (c) implementation; (d) evaluation and follow-up. The implementation of the training begins with an understanding of research school management, project and case-based learning, research-based learning approaches in the science, technology and social humanities groups. The results of the training show that there has been a change in Islamic boarding school application skills based on research by teachers. Furthermore, the implementation of research-based Islamic boarding schools is implemented with ongoing assistance so that maximum results can be obtained in its implementation. Keywords: Teachers; Training; Research Learning; Islamic Boarding Schools Based On Research.